Gymnasts utilize visual and auditory information for behavioural synchronization in trampolining - Heinen, T.; Koschnick, J.; Schmidt-Maaß, D.; Vinken, P. M. (Biology of Sport, 2014)
In synchronized trampolining, two gymnasts perform the same routine at the same time. While trained gymnasts are thought to coordinate their own movements with the movements of another gymnast by detecting relevant movement information, the question arises how visual and auditory information contribute to the emergence of synchronicity between both gymnasts. Therefore the aim of this study was to examine the role of visual and auditory information in the emergence of coordinated behaviour in synchronized trampolining. Twenty female gymnasts were asked to synchronize their leaps with the leaps of a model gymnast, while visual and auditory information was manipulated. The results revealed that gymnasts needed more leaps to reach synchronicity when only either auditory (12.9 leaps) or visual information (10.8 leaps) was available, as compared to when both auditory and visual information was available (8.1 leaps). It is concluded that visual and auditory information play significant roles in synchronized trampolining, whilst visual information seems to be the dominant source for emerging behavioural synchronization, and auditory information supports this emergence.